The Construction of Ethnopedagogy for Character Education: An Interpretative Phenomenological Analysis of the Samin Community - Nelly Marhayati; Suryani Suryani; Rodiyah Rodiyah; Ahmad Walid; Mifta Kharisma (Yayasan Keluarga Guru Mandiri, 2026)
Early childhood character education is a global imperative in mitigating the socio-moral erosion caused by rapid globalization, which often relies on Western-centric models while under-researching indigenous alternatives. Research objective: This study aims to investigate the ethnopedagogical framework of the Samin community in Indonesia to analyze how their resilient moral philosophy is transmitted to the younger generation. Utilizing a qualitative design with Interpretative Phenomenological Analysis (IPA), the research explores the subjective experiences of seven Samin parents in instilling character through in-depth interviews and participant observation. Findings reveal that character development is an indigenous-organic and informal process rooted in parental role modeling and daily social praxis, prioritizing core values such as radical honesty, collective responsibility, and social harmony. The Samin approach successfully integrates moral teaching into the fabric of cultural identity, demonstrating that informal education based on oral traditions serves as a primary foundation for children's moral growth. This study contributes to social science by illustrating how indigenous principles can be contextualized to strengthen moral frameworks, providing educators with a reference point for developing locally relevant, ethically driven pedagogical strategies.